(untitled) (AYUSHDHARA, 2025)
Polymyositis is an idiopathic inflammatory myopathy characterized by symmetrical proximal muscle weakness. Though not explicitly described in Ayurvedic texts, similar clinical features are observed in conditions like Apabahuka, classified under Vatavyadhi. This case highlights the role of Ayurvedic interventions in managing such neuromuscular disorders. Methods: A 63-year-old male presented with progressive upper limb weakness and cervical pain. Based on Ayurvedic clinical examination and Samprapti, treatment was initiated with Sthanika Abhyanga and Churna Pinda Sweda, followed by Sarvanga Abhyanga with Ksheerabala Taila and Shashtika Shali Pinda Sweda. Nasya was administered using Shadbindu Taila and Mahamasha Taila. Upon discharge, Uttarabhaktika Snehapana with Panchatikta Ghrita was advised. Results: The patient showed significant reduction in pain and stiffness, with marked improvement in muscle strength and daily functioning. Follow-up evaluations indicated sustained benefits and improved quality of life. Discussion: This case demonstrates the potential of Panchakarma therapies, particularly Vatahara and Brimhana modalities, in the management of polymyositis. Ayurvedic intervention provided functional recovery and symptomatic relief, validating its role in chronic neuromuscular conditions.